2020
DOI: 10.3389/fpsyg.2020.569078
|View full text |Cite
|
Sign up to set email alerts
|

Tracking the Influence of Predictive Cues on the Evaluation of Food Images: Volatility Enables Nudging

Abstract: In previous research on the evaluation of food images, we found that appetitive food images were rated higher following a positive prediction than following a negative prediction, and vice versa for aversive food images. The findings suggested an active confirmation bias. Here, we examine whether this influence from prediction depends on the evaluative polarization of the food images. Specifically, we divided the set of food images into "strong" and "mild" images by how polarized (i.e., extreme) their average … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
1
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 28 publications
(38 reference statements)
1
1
0
1
Order By: Relevance
“…Our analysis revealed that directional cues had a substantial effect on images that were clearly moral or immoral, leading to more extreme evaluations due to confirmation bias, corroborating our previous observations of confirmation bias in the evaluation of appetitive and aversive food images (Ounjai et al, 2018 , 2020 ). To examine the operation of a liminal confirmation bias in moral evaluation, we investigated the impact of predictive cues on the evaluation of neutral images which imply a different and more complex evaluation of moral properties.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Our analysis revealed that directional cues had a substantial effect on images that were clearly moral or immoral, leading to more extreme evaluations due to confirmation bias, corroborating our previous observations of confirmation bias in the evaluation of appetitive and aversive food images (Ounjai et al, 2018 , 2020 ). To examine the operation of a liminal confirmation bias in moral evaluation, we investigated the impact of predictive cues on the evaluation of neutral images which imply a different and more complex evaluation of moral properties.…”
Section: Discussionsupporting
confidence: 90%
“…The entire pattern of data suggested the operation of an active confirmation bias. In the follow-up study (Ounjai et al, 2020) we found that the predictive cues were most influential for food images that overall had relatively moderate rating scores. This finding suggested that the confirmation bias has a specific liminal influence, able to nudge the evaluation in a positive or negative direction particularly for stimuli near the boundary of neutrality.…”
Section: Introductionmentioning
confidence: 76%
“…หน้ า รู ปที ่ 1 รู ปทรงของไมโครพลาสติ กประเภททุ ติ ยภู มิ (secondary microplastics) ที ่ พบในทะเลสาบ Qinghai ในประเทศจี น (A) แผ่ น (B) ฟิ ล์ ม (C) เส้ นใย (D) ชิ ้ นส่ วน (E) เม็ ดกลม (F) โฟม (Wu et al, 2018) (Cole et al, 2011;Fendall & Sewell, 2009) และกลุ ่ มที ่ สองไมโครพลาสติ กทุ ติ ยภู มิ (secondary microplastics) ซึ ่ งเกิ ดจากพลาสติ กขนาดใหญ่ (macroplastic) ที ่ ลดขนาดจนมี ขนาดเล็ กกว่ า 5 มิ ลลิ เมตรจากกระบวนการทางกายภาพ ชี วภาพ และเคมี (Fotopoulou & Karapanagioti, 2017;Leja & Lewandowicz, 2010) (Imhof et al, 2017;Kim et al, 2015;Veerasingam et al, 2016) และปั จจั ยจากกิ จกรรมของ มนุ ษย์ (Sarafraz et al, 2016) (Ericsson, 2018;Ounjai et al, 2020;Ta & Babel, 2020) (Mato et al, 2001;Rochman et al, 2013) เนื ่ องจากขนาดที ่ เล็ กของไมโครพลาสติ กจึ งทำให้ สั ตว์ สามารถกิ นเข้ าไปได้ โดยตรงและมี การ ถ่ ายทอดผ่ านห่ วงโซ่ อาหาร จนอาจนำไปสู ่ การสะสมไมโครพลาสติ กในสิ ่ งมี ชี วิ ตในทะเล (Cole et al, 2020;Costa et al, 2020;Nadal et al, 2016;Neves et al, 2015;Setala et al, 2014;Tanaka & Takada, 2016) (Cole et al, 2019;Cole et al, 2015;Coppock et al, 2019) หอยแมลงภู ่ เขี ยว Perna viridis (Linnaeus, 1758) เป็ นหอยสองฝาที ่ มี ความสำคั ญทาง เศรษฐกิ จของประเทศไทย มี การนำหอยแมลงภู ่ มาใช้ กั นอย่ างแพร่ หลายในการประเมิ นความเสี ่ ยงที ่ เกิ ดจากมลพิ ษจากสิ ่ งแวดล้ อม (Beyer et al, 2017;Farrington et al, 2016;Li et al, 2019;Song et al, 2016) หอยแมลงภู ่ มี ลั กษณะการกิ นอาหารแบบกรองกิ นมี รายงานพบว่ ามี ความสามารถ ในการสะสมไมโครพลาสติ กด้ วยเช่ นกั น (Ward et al, 2019) โดยไมโครพลาสติ กอาจถู กดั กจั บโดย เหงื อกและ labial palpsและบางส่ วนอาจถู กกำจั ดออกทางมู ลเที ยม (Porter et al, 2018;Rosa et al, 2018;…”
Section: สารบั ญภาพunclassified